Vascular Reactivity, Chemical Profile, Toxicological And Pharmacokinetic Studies Of Andrographis Paniculata Nees. Extracts - Naidu, Sriramaneni Raghava (2009)
The aims of the study were to evaluate the vascular reactivity, chemical profile, toxicity and pharmacokinetic of Andrographis paniculata (AP) extracts. Tujuan kajian ini adalah untuk menilai reaktiviti vaskular, profil kimia, ketoksikan dan farmakokinetik ekstrak Andrographis paniculata.